Práticas emergentes de um novo paradigma de saúde: o papel da universidade - Santos, Jair Lício Ferreira; Westphal, Marcia Faria (Estudos Avançados, 1999)
HEALTH PRATICES have always been determined by the orienting paradigms of the health sciences, which in their turn refer partly to the country's global technological social economic context. The authors of this text aim at comparing the different paradigms which have been governing public health practices in the last two centuries and at defining in further details the evidence-based conception that health is a social product, opposing the Flexnerian curativistic paradigm. A further aim is to present new practices resulting from the new conception whose focal point is preventive attention to health. New types of action, such as health promotion, are described and analyzed, as well as the need to engraft the new vision on the old prevention and cure practices. The new paradigm structuring projects are outlined in the description of Towns/Healthy Counties and of the Family Health Program. Concluding, the role the university and mainly the public health colleges have been playing vis-a-vis the innovations of the paradigm and the practices it originates is analyzed.